Force, Torque and Stiffness: Interactions in Perceptual Discrimination - Wu, Bing (2011)
Three experiments investigated whether force and torque cues interact in haptic discrimination of force, torque and stiffness, and if so, how. The statistical relation between force and torque was manipulated across four experimental conditions: Either one type of cue varied while the other was constant, or both varied so as to be positively correlated, negatively correlated, or uncorrelated. Experiment 1 showed that the subjects’ ability to discriminate force was improved by positively correlated torque but impaired with uncorrelated torque, as compared to the constant torque condition. Corresponding effects were found in Experiment 2 for the influence of force on torque discrimination. These findings indicate that force and torque are integrated in perception, rather than being processed as separate dimensions. A further experiment demonstrated facilitation of stiffness discrimination by correlated force and torque, whether the correlation was positive or negative. The findings suggest new means of augmenting haptic feedback to facilitate perception of the properties of soft objects.